Promoting Family Involvement in the Management of Delirium in Intensive Care: Scoping Review - Sandra Lange; Wioletta Mędrzycka-Dąbrowska (Medicina)
Background: In recent years, family involvement in ICU patient care has become increasingly significant. Family involvement in delirium management, while desirable, can be difficult for loved ones. Therefore, every attempt should be made and interventions developed to promote and support the family in this process. The aim of this review was to analyze the available literature on interventions and strategies used by ICU staff to support and promote family involvement in the management of delirium in critically ill patients. Methods: The databases searched included the following: MEDLINE, CINAHL, and the Cochrane Library. Studies were included in the review if they were conducted in adult intensive care units and/or addressed interventions to support and promote family/relatives’ involvement in delirium management. Findings: A total of 368 database articles were reviewed. After removing duplicates and checking for inclusion and exclusion criteria, four articles were finally included in the analysis. Research gaps and content analysis identified promotional and supportive interventions for family involvement in delirium management: (I) Education; (II) Mentoring; (III) Partnership. Conclusions: Research gaps to be filled are as follows: (I) the scope of interventions that support and promote family involvement in delirium management; (II) interventions that enhance feelings of efficacy among family members and reduce symptoms of anxiety and depression; and (iii) the impact of specific interventions on patients’ delirium outcomes.